La communication entre collègues bouleversée par la pandémie et le développement du télétravail - Delphine Pauline Dupré (Communiquer)
The Covid-19 pandemic and the three successive lockdowns taking place in France during the years 2020 and 2021 have led to the development of telework in unprecedented proportions, as well as an upsurge in the uses of digital devices to compensate for the lack of co-presence. In this paper, we analyze to what extent the pandemic period has altered interpersonal communication between colleagues with equal hierarchical status. We wonder whether ICTs have been used to extend the “spaces of discussion” necessary to the emergence of social support, and to the transmission of the rules of the profession? This research draws on a qualitative enquiry based on 34 semi-structured interviews with teleworkers. Data analysis brings to the fore a feeling of isolation, a dehumanization of professional relations, as well as the trivialization of problematic digital practices. At the other end of the spectrum, respondents express positive views on relational distance (a decrease in conflicts, less disturbances in the work setting, refocusing on elective relationships). The factors leading to these contrasting opinions are brought into focus.